Neighborhood gentrification, wealth, and co-ethnic density associations with acculturation stressors among Chinese immigrants - Amy H. Auchincloss; Francesca Mucciaccio; Carolyn Y. Fang; Dominic A. Ruggiero; Jana A. Hirsch; Julia Zhong; Minzi Li; Brian L. Egleston; Marilyn Tseng (Elsevier, 2023)
Objective: This study examined the cross-sectional relationships between neighborhood social composition and gentrification, and acculturation stressors. Methods: Person-level data came from first-generation Chinese immigrants enrolled in the Immigrant Enclaves Study (Philadelphia, Pennsylvania, baseline 2018-2020, N = 512). A validated scale was used to assess 22 stressors associated with migration or acculturation. Neighborhood characteristics from the American Community Survey 2015-2019 and 2008-2012 included: tract proportion of foreign born Chinese, neighborhood wealth, and past decade gentrification. Most neighborhood exposures were modeled as continuous as well as binary variables (intended to represent highest level of neighborhood exposure). Multivariable negative binomial regression adjusted for age, gender, income, education, employment, language, years in the U.S., and neighborhood variables (proportion co-ethnic, and neighborhood per capita income). Results: The majority of participants spoke Mandarin (68% vs Cantonese 32%), mean participant age was 52.7 years old, years in the US was 18, and nearly one-half of the sample had less than 8 years of education. Mean number of stressors was 5.9 with nearly 20% of participants reporting 11 or more stressors. Multivariable results found the number of acculturation stressors was 18% lower for residents in the highest co-ethnic density neighborhoods and 13% lower for residents in the highest wealth areas, compared to other areas (expβ 0.82, 95% CI [CI] 0.69, 0.98; expβ 0.87, CI 0.75, 1.01, respectively). Stressors were no different whether participants lived in gentrified areas or not. Conclusions: Among middle-aged Chinese immigrants, acculturation stress was lower for residents in neighborhoods with higher proportion of Chinese immigrants and for residents in neighborhoods with higher wealth, whereas gentrification had no influence on acculturation stress. More work on this topic is needed with vulnerable populations such as this one, informed by local context.